Evaluation of GNSS as a tool for monitoring tropospheric water vapour - Ahmed, Furqan (My University, 2010)
Global Navigation Satellite Systems have the potential to become a significant tool in climate research due to the fact that GNSS data can be processed in order to estimate the propagation delay experienced by the signal in atmosphere. If the ground pressure and temperature is known, the signal propagation path delay can be related to the amount of water vapour in the atmosphere. This thesis project focuses on the evaluation of GNSS as a tool for atmospheric water vapour estimation. In the first part of the project, various GNSS data processing software packages were compared by processing the same set of data and performing a statistical comparison of the estimates of zenith total delay obtained by each package. The software packages compared are GIPSY‐OASIS, Bernese GNSS Processing Software, GAMIT and magicGNSS. Also different strategies and methods, such as double‐differencing and precise point positioning, are investigated. The output from the packages is validated using delay measurements obtained from ECMWF and RCA numerical models. It was observed that the output from climate models agrees with that from the software packages and the output from various software packages have a similarity between each other within 3 millimeters. In the second part of the project, simulations of new GNSS are carried out using in‐house software developed at Chalmers and SP Technical Research Institute of Sweden in order to investigate new methods and possible future improvements. The effect of local errors on atmospheric delay estimates from GPS, GLONASS and Galileo was studied through simulations. A hypothetical system formed by combination of the constellations of GPS, GLONASS and Galileo was also simulated and it was found to be least susceptible to local errors. Simulations were performed by varying some Keplerian orbital elements for Galileo system and it was observed that an orbit inclination between 60 and 65 degrees would have been optimum for Galileo system.
Keywords: Fysik; Physical Sciences